2021
DOI: 10.20945/2359-3997000000364
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in patients with advanced differentiated thyroid cancer treated with multikinase inhibitors – a single Brazilian center experience

Abstract: Objective: The aim of this study was to describe the real-world experience multikinase inhibitors (MKI) in the treatment advanced differentiated thyroid carcinoma (DTC) refractory to radioactive iodine (RAIR) therapy. Subjects and methods: We reviewed the records of all patients with MKItreated DTC from 2010 to 2018. Progression free survival (PFS), response rates (RR) and adverse events (AE) profiles were assessed. Clinical parameters were compared between groups with different outcomes (disease progression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(72 reference statements)
4
2
0
Order By: Relevance
“…In our cohort, patients who received sorafenib demonstrated an ORR of 9%. This aligns with ndings from other real-world studies, which have reported ORRs ranging from 11-25% [14][15][16][17], as well as with results from the DECISION trial, where patients exhibited a PR of 12% without any CRs [3]. In contrast, our group of patients treated with lenvatinib exhibited a lower ORR compared to what was reported in the SELECT phase III study and in non-trial settings (ranging from 33-69%) [4,[18][19][20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our cohort, patients who received sorafenib demonstrated an ORR of 9%. This aligns with ndings from other real-world studies, which have reported ORRs ranging from 11-25% [14][15][16][17], as well as with results from the DECISION trial, where patients exhibited a PR of 12% without any CRs [3]. In contrast, our group of patients treated with lenvatinib exhibited a lower ORR compared to what was reported in the SELECT phase III study and in non-trial settings (ranging from 33-69%) [4,[18][19][20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 91%
“…The adverse event (AE) pro les of sorafenib and lenvatinib observed in our study were consistent with ndings from clinical trials and other retrospective cohorts [3,4,[14][15][16][17][18][19][20][21][22][23][24][25]. Both tyrosine kinase inhibitors (TKIs) exhibited high percentages of AEs (97% with sorafenib and 100% with lenvatinib) and serious AEs (56% with sorafenib and 65% with lenvatinib), with no statistical difference observed between the groups.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Prognostic factors of better outcome with MKIs therapy were identified, such as the absence of 18FDG uptake on target lesions, lower maximum standardized uptake values on positron emission tomography (PET-CT), presence of lung-only metastasis, and lower Tg during treatment [ 86 ]. In lenvantinib-treated patients, the appearance of HFS was correlated with a good prognosis, as opposed to fistula formation or severe tumour regrowth after drug discontinuation, which were associated with poor prognosis [ 87 ].…”
Section: Radioiodine-refractory Dtcmentioning
confidence: 99%